Analisis Komparatif Kinerja Keuangan antara Bank Syariah dan Bank Konvensional Berdasarkan Metode Camel - Armanto Witjaksono; Anis Yunistriani (Binus Business Review, 2011)
The main objective of this paper is to give an overview of comparative financial performance of Islamic banks with conventional banks based on the CAMEL method. The main question would be answered to know there is difference in the performance of conventional banking and Islamic banking are analyzed by using the ratio CAMEL. To prove the hypothesis that there is no significant difference between the bank's financial performance Islamic and conventional banks (Ho) or there are significant differences between the financial performance of Islamic banks and conventional banks (Hi). Researchers used a parametric statistical technique, which consists of test data normality using the Kolmogorov Smirnov test and QQ plots, test of homogeneity using the F test (Levene's Test), and Independent Sample T-Test with significant value 5% confidence level (1 - α) = 95%. The results showed that the ratio of data CAMEL Islamic banks and conventional banks in normal distribution and homogeneous. Then it can be concluded that the variable CAR, NPL, and LDR between conventional banks and Islamic banks have significant differences, while the ROA and ROE of the two types of banking industry is not significantly different or relatively the same.